Directions for improving the legal regulation of forensic DNA analysis in Ukraine in the context of integration into the European Union - Stepaniuk, R. L.; Kikinchuk, V. V. (Bulletin of Kharkiv National University of Internal Affairs, 2022)
An analysis of European standards and main trends in the field of legal regulation of forensic DNA analysis has been carried out. It has been established that the general European legislation defines recommendations on the general principles of using DNA analysis within the framework of the criminal justice system, establishes the obligation of each state to create and maintain a national DNA database, exchange information based on DNA databases, take measures to protect personal data, store DNA profiles of persons convicted of sexual offenses against children, to accredit forensic laboratories to ensure the proper quality of molecular genetic research. Taking into account the experience of European countries, it can be seen that a comprehensive approach to the improvement of domestic legislation, namely the implementation of the law on the national DNA database, the introduction of amendments and additions to the current Code of Criminal Procedure of Ukraine, other laws and departmental regulations regarding the use of DNA analysis in criminal proceedings, is a necessary prerequisite for bringing this area of law enforcement to a new qualitative level. Together with the adoption of the Law of Ukraine “On the State Registration of Human Genomic Information”, it is necessary to introduce changes and additions to the Code of Criminal Procedure of Ukraine in order to harmonize the provisions of these normative legal acts, which primarily concern the improvement of the procedure for obtaining samples for molecular genetic research. It has been substantiated that the experience of Germany and the Netherlands regarding the legal regulation of mass DNA testing at the stage of pre-trial investigation of serious and especially serious crimes can be useful for Ukraine. Taking into account the rapid development of forensic DNA analysis technologies and the introduction of the latest methods, which are characterized by a much greater degree of interference in the personal and family life of a person, compared to traditional methods of STR profiling, there is a need for a legislative definition of the permissible limits of forensic DNA research within the framework of criminal proceedings in Ukraine.